What drives the energy saving role of FDI and industrialization in East Africa? - Adom, Philip Kofi; Amuakwa-Mensah, Franklin (Renewable & sustainable energy reviews, 2016)
Analysis of the unconditional impacts of foreign direct inflows (FDIs) and industrialization on energy intensity does not show the hidden roles of some economic conditions such as income and trade openness. In this study, we focused on the conditional impacts of FDIs and industrialization on energy productivity using a panel data consisting of thirteen (13) East African countries covering 1980–2011. The baseline result shows that higher income and a well-integrated economy are pro-energy productive, but FDIs and intense industrialization are anti-energy productive in the sub-region. This result remains robust even when we exclude the high income group and control for income group effects. Income significantly promotes energy productivity more in low income group than middle income group. Intense industrialization and FDIs significantly decreases energy productivity only in low income countries. Trade openness significantly promotes energy productivity only in middle income group. We have shown that FDIs and income, intense industrialization and FDIs, and intense industrialization and globalization are complementary forces that promote energy productivity in East Africa but this is more evident for the middle income group than the low income group in the sub-region. Based on the result, we recommend a quadruplet programme called the “Growth, Industrial, Foreign investment and Trade programme” (GIFTP). Last, our result suggests that unconditional analysis of energy productivity should not be seen as an end in itself but a basis for further analysis. •Investigates what drives the energy savings in FDIs and industrialization.•FDIs and industrialization reinforce each other to enhance energy productivity.•Globalization and industrialization reinforce each other to promote energy productivity.•Income and FDIs reinforce each other to promote energy productivity.